Eicosapentaenoic acid and arachidonic acid differentially regulate adipogenesis, acquisition of a brite phenotype and mitochondrial function in primary human adipocytes. Issue 9 (9th June 2016) - Fleckenstein‐Elsen, Manuela; Dinnies, Daniela; Jelenik, Tomas; Roden, Michael; Romacho, Tania; Eckel, Jürgen
Abstract : Dietary long‐chain polyunsaturated fatty acids (LC‐PUFAs) have been proposed to modulate adipocyte function. The n‐6 PUFA arachidonic acid (ARA) reduces metabolic flexibility and enhances the white marker Tcf21 during differentiation. The n‐3 PUFA eicosapentaenoic acid (EPA) improves citrate synthase activity and higher maximal respiratory capacity during differentiation. The markers of energy‐burning brite cells UCP‐1 and CPT1B are increased by EPA in both preadipocytes and adipocytes. Abstract : Scope: n‐3 and n‐6 PUFAs have several opposing biological effects and influence white adipose tissue (WAT) function. The recent discovery of thermogenic UCP1‐expressing brite adipocytes within WAT raised the question whether n‐3 and n‐6 PUFAs exert differential effects on brite adipocyte formation and mitochondrial function. Methods and results: Primary human preadipocytes were treated with n‐3 PUFAs (eicosapentaenoic acid, EPA; docosahexaenoic acid, DHA) or n‐6 PUFA (arachidonic acid, ARA) during differentiation, and adipogenesis, white and brite gene expression markers, mitochondrial content and function were analyzed at day 12 of differentiation. Adipogenesis was equally increased by n‐3 and n‐6 PUFAs. The n‐6 PUFA ARA increased lipid droplet size and expression of the white‐specific marker TCF21 while decreased mitochondrial protein expression and respiratory function. In contrast, EPA increased expression of the brown adipocyte‐related genes UCP1 and CPT1B, and improved mitochondrial function of adipocytes. The opposing effects of EPA and ARA on gene expression and mitochondrial function were also observed in cells treated from day 8 to 12 of adipocyte differentiation. Conclusion: EPA promotes brite adipogenesis and improves parameters of mitochondrial function, such as increased expression of CPTB1, citrate synthase activity and higher maximal respiratory capacity, while ARA reduced mitochondrial spare respiratory capacity in vitro.